2017
DOI: 10.3748/wjg.v23.i16.2854
|View full text |Cite
|
Sign up to set email alerts
|

Importance of antimicrobial susceptibility testing for the management of eradication inHelicobacter pyloriinfection

Abstract: The management of Helicobacter pylori (H. pylori) infection treatment differs from the common treatment protocol for other infectious diseases. Because culture- or molecular-guided approaches face several practical issues, such as the invasive procedures required to obtain gastric biopsy specimens and the lack of availability of routine laboratory testing in some places, H. pylori treatment includes the administration of two or three empirically selected antibiotics combined with a proton pump inhibitor rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
69
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 89 publications
(412 reference statements)
2
69
0
2
Order By: Relevance
“…Phenotypic assays of determining antibiotic susceptibility including gradient diffusion susceptibility testing (E-test) and the agar dilution method are time-consuming, expensive, and not routine [13]. Therefore, molecular-based techniques such as PCR-restriction fragment length polymorphism (RFLP), real-time PCR, and fluorescence in situ hybridization (FISH) are appropriate alternatives to the phenotypic methods and can also detect point mutations associated with the antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotypic assays of determining antibiotic susceptibility including gradient diffusion susceptibility testing (E-test) and the agar dilution method are time-consuming, expensive, and not routine [13]. Therefore, molecular-based techniques such as PCR-restriction fragment length polymorphism (RFLP), real-time PCR, and fluorescence in situ hybridization (FISH) are appropriate alternatives to the phenotypic methods and can also detect point mutations associated with the antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, molecular-based techniques such as PCR-restriction fragment length polymorphism (RFLP), real-time PCR, and fluorescence in situ hybridization (FISH) are appropriate alternatives to the phenotypic methods and can also detect point mutations associated with the antibiotic resistance. FISH is a new technology based on fluorescently labeled DNA probes that hybridize with specific rRNA sequences of microorganisms and can identify H. pylori and resistance to clarithromycin in formalin-fixed paraffin-embedded tissue sections or cultured H. pylori colonies [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori has been associated with the development of multiple gastrointestinal diseases such as dyspepsia, peptic ulcer, chronic gastritis, MALT gastric lymphoma, and gastric cancer [1]. H. pylori infections are treated with different antimicrobials such as clarithromycin, metronidazole, amoxicillin, tetracycline, ciprofloxacin, levofloxacin, moxifloxacin, azithromycin, erythromycin, furazolidone, and nitrofurantoin [2][3][4][5], which are combined with a proton pump inhibitor (PPI) to increase their absorption in the stomach of the patient [5,6]. In Colombia, infection eradication therapy is empirical, in which the first-line treatment is the clarithromycin-based standard triple therapy (clarithromycin, amoxicillin and PPIs), agreeing to national and international guidelines [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In Colombia, infection eradication therapy is empirical, in which the first-line treatment is the clarithromycin-based standard triple therapy (clarithromycin, amoxicillin and PPIs), agreeing to national and international guidelines [7][8][9]. Resistance rates have increased in many countries, which warrant a continuous study of the H. pylori resistance rates worldwide and regionally [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is suggested to identify the H. pylori strains that are likely to fail empirical therapy and subsequently to choose a personalized therapeutic regimen with high likelihood of successful eradication. Several studies have reported that a treatment based on antimicrobial susceptibility testing is more effective than empirical treatment (15)(16)(17).…”
mentioning
confidence: 99%